HALAL FOOD SUPPLY MOTIVATION FOR MUSLIM PATIENTS - Primasari, Elsa; Sulistiadi, Wahyu (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: The obligation of consuming halal food for muslims as a religious requirement. Unfortunately in Indonesia not all hospital provide health service that are capable of providing halal food and offering Halal certification food. This might cause patient to feel distrust and discomfort. Therefore, all reliable stakeholder are expected to have the motivation and commitment to guarantee halal food in the hospital services. This study aimed to analyze the providers? (hospitals?) motivation to provide halal food for their Muslim patients according to Islamic rule.Methods: This study employed a systematic review to observe articles related to halal food awareness and halal food certification in Indonesia and other countries that serve Muslim consumers, which have been published online in the accredited journal, such as Scopus journals, ProQuest journals, and Google Scholar. The inclusion criteria employed in this study were halal Food, certification, academic journals, and full papers. This searching was limited to articles in the last ten years, except the articles which are not related to the theme. PRISMA method was implemented to assess the selected articles critically. The article searching was based on Halal Food keywords in ProQuest, Scopus, and Google Scholar. The full inclusion tests resulted in one thousand three hundred seventy articles; however, after conducting the inclusion and exclusion, the researcher obtained five articles.Results: The researchers found that hospitals, both in the Muslim majority and minority places, were not fully aware of halal food services. Nevertheless, few Islamic hospitals have Halal Assurance certification in providing their food due to the Sharia accreditation requirement. The low interest in obtaining the Halal Guarantee certification was due to several problems, such as lack of knowledge about halal, financial problems, and government support.Conclusions: The need of awareness of hospital as a health service provider to provide a halal food for muslim patient by participating in the implementation of Halal Food Guarantee Certification.